The effect of a running training intervention on ankle power generation in children and adolescents with cerebral palsy: A randomized controlled trial. (June 2020) - Chappell, A.; Allison, G.T.; Williams, G.; Gibson, N.; Morris, S.
Abstract: Background: Children and adolescents with cerebral palsy who are classified as Gross Motor Function Classification Scale level I or II are usually able to run but lack ankle power generation for push-off. The aim of this study was to analyze the efficacy of a running training program in improving ankle power generation in children and adolescents with cerebral palsy. Methods: This randomized controlled trial compared kinematic and spatiotemporal data collected during running from 38 children and adolescents with unilateral or bilateral cerebral palsy before and after a 12-week running program. Normalized speed, stride length, cadence, foot strike pattern, peak ankle power generation, peak hip flexor power generation in swing and propulsion strategy were calculated. Linear mixed models were developed to analyze differences between groups. Findings: At follow-up the intervention group had increased normalized speed of running ( t  = −3.68 p  < .01) while the control group got slower ( t  = 3.17 p  < .01). In running, children in Gross Motor Function Classification Scale level II in the intervention group increased ankle power ( t  = 2.49 p  = .01) while the control group did not change ( t  = 0.38 p  = .71). In sprinting, children in Gross Motor Function Classification Scale levels I and II in the intervention group maintained ankle power (level I t  = 0.32 p  = .75; level II t  = 1.56 p  = .12) while those in the control group decreased ankle power (level I t  = 4.69 p  < .01; level II t  = 2.52 p  = .01). Most within-group differences did not result in significant between-group differences at follow-up. Interpretation: Power generation for running may be responsive to targeted intervention in children with cerebral palsy. Highlights: Ankle power generation may respond to intervention in children with cerebral palsy. Intervention may normalize the propulsion strategy in children with cerebral palsy. Response to intervention may depend on baseline functional level.